Molybdenum disulfide side-polished fiber saturable absorber Q-switched fiber laser - Ahmad, Harith; Hassan, H.; Safaei, R.; Thambiratnam, K.; Ismail, M.F.; Amiri, I.S. (Elsevier, 2017)
A Q-switched fiber laser based on a Molybdenum disulfide (MoS2) saturable absorber (SA) is proposed and demonstrated. A 3 m long erbium-doped fiber with an absorption coefficient of 11.3 dB/m at 979 nm acts as the linear gain medium of the laser. The SA is formed by depositing a MoS2 layer on a self-fabricated side-polished fiber (SPF), which can be easily fabricated in less than 15 min. The proposed laser has a Q-switching threshold of 14.8 mW, and is capable of generating a pulsed output with a repetition rate and pulse-width of up to 25.27 kHz and 3.19 μs at a maximum pump power of 45.6 mW, as well as an average output power and pulse energy of 2.27 mW and 0.09 μJ at the same pump power. The pulses have an average signal-to-noise ratio of 37.8 dB, indicating a stable output and making the proposed laser highly suited for a variety of sensor, communications, and industrial applications.